"Maritime security and the need for a maritime offenses law in Malaysia: a critical appraisal" - Hamid, Abdul Ghafur@Khin Maung Sein (2015)
Maritime security is a major concern for Malaysia and other South East Asian nations. This paper first of all assesses the seriousness of maritime security threats in Malaysian waters and identifies the major maritime offences that need to be dealt with according to law. The paper carries out an in-depth analysis of the relevant Malaysian laws in order to prove that there is indeed a legal vacuum to cope with maritime offences in Malaysia. The doctrinal analysis of the laws are supplemented by the results of roundtable discussions and interviews with experts from maritime law enforcement agencies. The paper finds that the Penal Code, the principal substantive criminal law in Malaysia, is basically applicable only within the 12-mile territorial sea of Malaysia and is useless in the case of maritime offenses committed without and beyond Malaysia. What makes the matter worse is that unlike many countries in the world Malaysia has no specific piracy statute. The paper evaluates and analyses the laws of selected countries, such as the Maritime Offences Act 2003 of Singapore, and the Crimes (Ships and Fixed Platforms) Act 1992 of Australia and also explores the CMI Model Law on Acts of Piracy and Maritime Violence. The paper concludes with recommendations on proposed draft Maritime Offences Bill to be recommended to the Government of Malaysia.